PENGARUH SISTEM INFORMASI AKUNTANSI MANAJEMEN DAN TEKNOLOGI INFORMASI TERHADAP KINERJA MANAJERIAL (Studi Empiris pada Hotel bintang 4 Di Provinsi Riau) - Adinata, Satria; -, Andreas; Savitri, Enni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study Aimed to analyze the effect of management accounting information systems and information technology to managerial performance 4 star hotel company in Riau, And To Obtain empirical evidence about the influence of management accounting information system on managerial performance. Population in this research is the fourth company in Riau, a total of 7 samples tested hotel company. Methods of Data collection using sampling Purposiv. The research of data was acquired seven companies that meet krikteria as this. from research managers and employees at the company’s hospitality. The type of the data used is primary. Data collection methods are surveys, questionnaires, this hypothesis using multiple linear regression analysis.The results Showed that the accounting information system management have a significant effect on the performance of managerial, information technology otherwise no effect on managerial performance.Keywords: management, accounting, information systems, technology, and performance.